A conceptual framework for ecological responses to groundwater regime alteration (FERGRA). Issue 7 (7th August 2018) - Kath, Jarrod; Boulton, Andrew J.; Harrison, Evan T.; Dyer, Fiona J.
Abstract: Globally, the provision of groundwater‐supported ecosystem services is threatened by climate change, water extraction, and other activities that alter groundwater regimes (defined as temporal dynamics in groundwater pressures, storage, and levels). Research on how altered groundwater regimes affect the ecology and ecosystem services of diverse groundwater‐dependent ecosystems (GDEs) is currently fragmented with little integration across different GDEs, hampering our ability to understand and manage ecological responses to anthropogenic changes to groundwater regimes. To address this, we present a framework for assessing ecological responses to groundwater regime alteration (FERGRA). FERGRA is a logical approach to investigating how alterations to groundwater regimes change the timing, variability, duration, frequency, and magnitude of groundwater connections to different GDEs, in turn affecting their ecological processes and ecosystem service provision. Using FERGRA, multiple GDEs can be assessed concurrently, optimizing their integrated management. Unifying the concepts of ecological responses to altered groundwater regimes and groundwater connections of different GDEs across the landscape, FERGRA provides a framework for (a) organizing the currently fragmented research on GDEs to better identify commonalities and knowledge gaps, (b) formulating and testing hypotheses for quantifying ecological responses to groundwater regime alteration in GDEs to derive general principles to guide research and management, and (c) facilitating assessments of the trade‐offs between the benefits of groundwater extraction (e.g., to support mining and agriculture) versus conservation of GDEs to protect other ecosystem services.